Prospective history teachers' information behaviour in lesson planning - Tanni, Mikko; Sormunen, Eero; Syvänen, Antti (Information Research, 2008)
Introduction. Information literacy education tends to take for granted teachers' own information literacy and their ability to integrate the Internet in teaching to facilitate students' information literacy. The article reports the results of a pilot study investigating young teacher trainees' information behaviour in lesson planning. Method. Fourteen prospective history teachers were interviewed individually in April 2007. Analysis. Content analysis was conducted on transcribed interviews. Atlas.ti qualitative data analysis software was used to segment, compare and organize the data. Results. At the end of the training period the teacher trainees were relatively fluent and versatile information seekers who were able to cope with the challenges of lesson planning and support textbooks with information retrieved from various information sources. Conclusions. The results indicate that the trainees had the necessary skills to seek and use information for lesson plans. The results opened promising paths to pursue research on the trainees' information behaviour further, to address their potential as information literacy instructors.